2011
DOI: 10.1016/j.jnci.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

High expression of LMO2 in Hodgkin, Burkitt and germinal center diffuse large B cell lymphomas

Abstract: LMO2 expression is a special feature of GC DLBCL which can be used as a diagnostic marker and therapeutic target. Further studies regarding its prognostic role in patients are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…An increasing number of studies have shown that lymphoma is considered the fourth most common tumor in Egypt; in particular, in adults, it represents 76.6% NHL and 23.4% HL [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have shown that lymphoma is considered the fourth most common tumor in Egypt; in particular, in adults, it represents 76.6% NHL and 23.4% HL [1].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, NHLs prevalence is about 4% of all diagnosed cancer and rank seventh in frequency among all cancers. Furthermore, many studies have shown that Original research lymphoma is considered the fourth most common tumor in Egypt, particularly in adults [1].…”
Section: Introductionmentioning
confidence: 99%
“…These cells can be found in the bone marrow, lymph nodes, spleen, thymus, and other organs. During lymphoma, lymphocytes alter and proliferate uncontrollably (1) .…”
Section: Introductionmentioning
confidence: 99%